Formability prediction of Ti6Al4V titanium alloy sheet deformed at room temperature and 600 °C - Bressan J.D.* (2021)
© 2020, Springer-Verlag France SAS, part of Springer Nature.Formability predictions of Ti6Al4V titanium alloy sheets deformed at room temperature and 600 °C, using D-Bressan’s shear stress rupture criterion and the critical strain gradient macroscopic modelling are presented and discussed in relation to limit strain results obtained experimentally. Ti6Al4V Forming Limit Strain Curves were predicted and compared with experimental curves at 25 °C and 600 °C and strain rate 0.1 s−1. The analytical models were calibrated by means of tensile tests performed on samples cut at 0°, 45° and 90° to the rolling direction at different temperatures and strain rates to obtain the Lankford coefficients and material strain and strain rate hardening behavior. The applied critical shear stress rupture criterion showed to give a fairly good fit with experimental limit strains outcomes, proving that the shear stress rupture nature of specimens deformed at room and elevated temperatures were well reproduced, despite a not-null strain rate sensitivity coefficient at 600 °C. Fracture occurrence by fast shear stress mechanism through thickness direction was corroborated by experimental fractograph observations close to fracture surfaces. It was shown that predicted limiting major true strain of fracture by shear stress curve is governed by normal anisotropy, strain hardening exponent, pre-strain and normalized critical shear stress parameter, which depends on temperature and strain rate whereas the strain hardening exponent depends largely on temperature. In contrast, the critical strain gradient modelling for onset of localized necking showed poor correlation with the experimental limit strains. Best fit of the critical shear stress criterion with experimental limit strain curves was given by specimens deformed near plane strain or FLCo. Hence, a common feature of various strain-rate independent metals, annealed or cold rolled, is that the main fracture mechanism of thin sheet metals can be considered as fast shear stress through sheet thickness without a visible localized necking in biaxial stretching.